The dynamics of shoreline change analysis based on the integration of remote sensing and geographic information system (GIS) techniques in Pekalongan coastal area, Central Java, Indonesia - Fajar Yulianto; S Suwarsono; Taufik Maulana; Muhammad Rokhis Khomarudin (Brawijaya University, 2019)
Coastal areas are found in the dynamic zone at the interface between the three major natural systems of the Earth's surface. The phenomenon of shoreline change is one of the most frequent problems encountered in the coastal environment and is caused by natural processes that result in dynamic changes in the coastal area. Coastal area change can affect the vulnerability of the coastal environment and its properties, such as shoreline stabilization, flood control, sediment retention, natural protection and others. The method of integrating remote sensing data with geographic information system (GIS) techniques has been widely used to monitor and analyze the dynamics of shoreline change in coastal areas. The purpose of this study is to map and analyze the dynamics of shoreline change from 1978 to 2017 in the study area. An approach combining spectral value index and visual interpretation of Landsat images was used and proposed to indicate the separation of land and water bodies, for shoreline extraction. The normalized difference water index (NDWI) can be used as a spectral value index approach for differentiating land and water bodies. Furthermore, the analysis of shoreline changes was performed using the digital shoreline analysis system (DSAS). Based on calculations made using DSAS, it can be seen that the pattern of coastline change tends to be dominated by offshore erosion. The results of this study may also be important as input data for coastal hazard assessment as part of the effort to overcome the problem of flood tides.